Исследование пропускной способности транспортного протокола TCP в спутниковых каналах связи - Калоша, В. А.; Москаленко, А. А. (Weber, 2010)
Comparative analysis of capacity for different implementations of TCP transport protocol is implemented, which depends on the parameters of communication channel.
Keywords: транспортный протокол; спутниковый канал связи